How to ride like a cowgirl : A study on the types of euphemistic language used by sex educators on the social media platform TikTok - Yli-Olli, Silja (My University, 2024)
The topic of this thesis is the euphemistic language use of sex educators on the social media platform TikTok. The aim is to observe what the types of euphemistic language used to avoid the removal or limitation of content related to sex education are, as well as the reasons behind the language use itself. The material of the thesis was collected from TikTok according to the principles of digital ethnography. The goal was to gain a realistic sense of euphemistic communication on the platform through the collection of short samples that included euphemistic language items from the spoken language of sex education content creators. The samples were analysed by sorting them into different categories of euphemistic language based on their level of lexicalisation. The level of lexicalisation determines how fixed in the lexicon the euphemistic meaning of a euphemistic language item is. The categories were Explicit, Conventional, Novel/artful, and ‘Other’, where Explicit was the most lexicalised and Novel/artful the least. The ‘Other’ category was created for items that did not fit into the other established categories. The results of the research show that certain types of euphemistic language were more frequent than others. The most common category of a euphemistic language item was the Conventional category, followed by the Novel/artful and Explicit ones. The main reasons behind the frequency of the categories were linked to their level of lexicalisation and the content creators’ need to avoid the removal of their content from TikTok.
Keywords: social media, TikTok, digital ethnography, euphemism, dysphemism, lexicalisation